# hw10 - MA341 Homework 10 Solution 7.5 9 z 00 5 z 6 z = 21 e...

This preview shows pages 1–2. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: MA341 Homework 10 Solution 7.5 9. z 00 + 5 z- 6 z = 21 e t- 1 ; z (1) =- 1, z (1) = 9 (1) To use the method of Laplace transforms, we first move the initial conditions to t = 0. This can be done by setting y ( t ) = z ( t + 1). Then, y ( t ) = z ( t + 1) , y 00 ( t ) = z 00 ( t + 1) . Replacing t by t + 1 in the differential equation in (1), we have: z 00 ( t + 1) + 5 z ( t + 1)- 6 z ( t + 1) = 21 e ( t +1)- 1 . (2) Substituting y ( t ) = z ( t + 1) in (2), we transform the initial value problem (1) into y 00 ( t ) + 5 y ( t )- 6 y ( t ) = 21 e t ; y (0) =- 1 , y (0) = 9 . (3) Next, we apply the Laplace transform to the differential equation in (3): L{ y 00 + 5 y- 6 y } = L{ 21 e t } . Using the linearity of L and applying the transform to the exponential function, we write: L{ y 00 } + 5 L{ y } - 6 L{ y } = 21 s- 1 . (4) Now let Y ( s ) := L{ y } ( s ). Applying the Laplace transform to the first and second derivatives: y and y 00 , and taking into account the initial conditions in (3), we find: L{ y } ( s ) = sY ( s )- y (0) = sY ( s ) + 1 , L{ y 00 } ( s ) = s 2 Y ( s )- sy (0)- y (0) = s 2 Y ( s ) + s- 9 . Then, substituting these expressions into (4) and solving for Y ( s ), we get: [ s 2 Y ( s ) + s- 9] + 5[ sY ( s ) + 1]- 6 Y ( s ) = 21 s- 1 ( s 2 + 5 s- 6) Y ( s ) =- s 2 + 5 s + 17 s- 1 Y ( s ) =- s 2 + 5 s + 17 ( s- 1)( s 2 + 5 s- 6) Y ( s ) =- s 2 + 5 s + 17 ( s- 1) 2 ( s + 6) . The expansion of Y ( s ) into partial fractions has the form:- s 2 + 5 s + 17 ( s- 1) 2 ( s + 6) = A s- 1 + B ( s- 1) 2 + C s + 6 . (5) Solving for the numerators, we eventually obtain: A = 0, B = 3, and C =- 1. Substitution of these values into (5) yields: Y ( s ) = 3 ( s- 1) 2- 1 s + 6 . Finally, using the tables of the Laplace transform we obtain: y ( t ) = 3 te t- e- 6 t . (6) Since z ( t + 1) = y ( t ), then z ( t ) = y ( t- 1). Hence, replacing t by t- 1 in (6) we find the solution of the IVP (1): z ( t ) = 3( t- 1) e t- 1...
View Full Document

## This homework help was uploaded on 04/16/2008 for the course MA 341 taught by Professor Schecter during the Spring '08 term at N.C. State.

### Page1 / 5

hw10 - MA341 Homework 10 Solution 7.5 9 z 00 5 z 6 z = 21 e...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online